Motivasi Multidimensional Siswa dalam Pembelajaran Bahasa Arab: Sebuah Studi Mixed Method - Robby Jundi Lestari; Nor Ainun; Muhammad Fajrian; Fathurahman Fathurahman; Rovi Lusmiati (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study investigates the complex multidimensional motivation of students in Arabic language learning (ALL) within a religious school context (Madrasah), addressing the gap between high intrinsic interest and inconsistent self-regulated learning. Using a mixed-methods design, data were collected through surveys, interviews, and observations from 60 students at MTsN 03 Sarolangun. The findings reveal that motivation is multidimensional, dominated by Religious Motivation (Very High), which acts as a collective source of energy and spiritual capital for potential self-regulation (Spiritual-Driven Self-Regulation / SDSR). However, Academic and Intrinsic Motivation are constrained by low self-regulated learning (65%) and a strong focus on grades. This goal-oriented behavior is classified as Performance Goal Orientation, indicating that motivation remains at the Identified Regulation stage, not yet achieving the stable Integrated Regulation phase of the Self-Determination Theory (SDT) continuum. The study concludes that sustainable motivation requires a pedagogical shift: teachers must transition the focus from performance to Mastery Goals by consistently implementing instructional strategies that emphasize Task Orientation and Autonomy Support. This intervention is crucial to foster sustainable self-initiated learning behavior.